PERAN DAN STRATEGI KOMUNIKASI JARINGAN MEDIA KOMUNITAS DALAM MENDORONG PARTISIPASI RADIO KOMUNITAS PADA PEMBANGUNAN DI KABUPATEN GUNUNGKIDUL - , Nurul Purnamasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A good governanced country whose citizens that are able to access information from mass media in order to increase its citizenâs capacity and prosperity. But in fact, (mainstream) mass media in Indonesia is full of economical oriented and political interests. In the other hand, community radio could play important role and can be the answer for ideal mass media function and role as a result of the democratization process for media. Community radios establish an association from district to national level. The research purposes were analyzing the role of the community media network developed by Jaringan Media Komunitas Gunungkidul (JMKGK) and their strategy of communication to encourage the community radios participation for development in Gunungkidul Regency. The research method used qualitative approach. Quantitative data was only needed for explaining specific information. The research results show that the community media network has formed of social capital to encouraging the members, in this case are community radio, to support the development from the grass root group level in order to give domino effect for development participation at higher level. JMKGK required the design of strategy of communication to strengthen the organization and improved their bargaining position when they have program sharing with government and non-government organization on development programs in Gunungkidul Regency.